2012
DOI: 10.1021/nn2050449
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanowire-Based Molecular Beacons for High-Sensitivity and Sequence-Specific DNA Multiplexed Analysis

Abstract: Nanomaterial-based molecular beacons (nanoMBs) have been extensively explored due to unique merits of nanostructures, including gold nanoparticle (AuNP)-, carbon nanotube (CNT)-, and graphene-based nanoMBs. Those nanoMBs are well-studied; however, they possess relatively poor salt stability or low specificity, limiting their wide applications. Here, we present a novel kind of multicolor silicon-based nanoMBs by using AuNP-decorated silicon nanowires as high-performance quenchers. Significantly, the nanoMBs fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 56 publications
1
87
0
1
Order By: Relevance
“…The limits of detection (LOD) of the targets calculated according to the 3δ were 75 pM for T1, and 62 pM for T2. Which is comparable or more sensitive than most of the methods previously reported for multiplexed analysis of DNA by AuNPs, GO, carbon nanotube and silicon nanowire [10,11,13,15] (See table S1, ESM). These results indicated that g-C 3 N 4 based multicolor nanoprobes can be applied to quantify multiple analytes with high sensitivity in homogenous solution.…”
Section: Multiplexed Dna Detectionmentioning
confidence: 72%
See 1 more Smart Citation
“…The limits of detection (LOD) of the targets calculated according to the 3δ were 75 pM for T1, and 62 pM for T2. Which is comparable or more sensitive than most of the methods previously reported for multiplexed analysis of DNA by AuNPs, GO, carbon nanotube and silicon nanowire [10,11,13,15] (See table S1, ESM). These results indicated that g-C 3 N 4 based multicolor nanoprobes can be applied to quantify multiple analytes with high sensitivity in homogenous solution.…”
Section: Multiplexed Dna Detectionmentioning
confidence: 72%
“…Fan et al reported using gold nanoparticles (AuNPs) to construct multicolor nanoscale molecular beacon for sequence specific nucleic acid analysis [10]. Carbon nanomaterial such as graphene oxide (GO) and carbon nanotube have been also exploited to develop multicolor fluorescent nanoprobes for multiplexed analysis of DNA [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to SiNWs-based FET, scientists have made tremendous effort for designing SiNW-based optical biosensors (e.g., fluorescent-and SERS-based biosensors) for detection of tumor-suppressor genes in sensitive, specific and reproducible manners. In 2012, He and coworkers employed silicon nanohybrids made of AuNPs@SiNWs for constructing novel molecular beacons (nanoMBs) with robust salt stability and high fluorescence quenching efficiency (> 90%) [48]. In comparison with free AuNPs which were prone to be aggregated in low-concentration (e.g., 0.01 M) salt solution, the SiNW-based nanoMBs preserved robust stability at a high concentration of salt solution (i.e., 0.1 M).…”
Section: Silicon Nanomaterial-based Biosensors For Cancer Diagnosismentioning
confidence: 99%
“…Of particular significance, the resultant SiNWs-based MBs were highly stable in solutions with high salt concentrations (e.g., 0.1 M) and in a wide temperature range (e.g., 10-80°C). Besides, the silicon MBs were suitable for simultaneously assembling various DNA strands due to huge surface of the prepared AuNPs-coated SiNW, allowing sensitive and multiplexed DNA detection at *pM levels [113].…”
Section: Fluorescence-based Biosensorsmentioning
confidence: 99%